2021
DOI: 10.3390/biology10020141
|View full text |Cite
|
Sign up to set email alerts
|

Cytochalasin B-Induced Membrane Vesicles from Human Mesenchymal Stem Cells Overexpressing IL2 Are Able to Stimulate CD8+ T-Killers to Kill Human Triple Negative Breast Cancer Cells

Abstract: Interleukin 2 (IL2) was one of the first cytokines used for cancer treatment due to its ability to stimulate anti-cancer immunity. However, recombinant IL2-based therapy is associated with high systemic toxicity and activation of regulatory T-cells, which are associated with the pro-tumor immune response. One of the current trends for the delivery of anticancer agents is the use of extracellular vesicles (EVs), which can carry and transfer biologically active cargos into cells. The use of EVs can increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 86 publications
(95 reference statements)
2
20
0
Order By: Relevance
“…Indeed, the MSCderived CINVs retained their surface protein architecture well, which suggested their suitability for the creation of CINVs. These data are in good agreement with previous observations [36,46,76].…”
Section: Isolation and Characterization Of Evs And Cinvssupporting
confidence: 93%
“…Indeed, the MSCderived CINVs retained their surface protein architecture well, which suggested their suitability for the creation of CINVs. These data are in good agreement with previous observations [36,46,76].…”
Section: Isolation and Characterization Of Evs And Cinvssupporting
confidence: 93%
“…On the one hand, the exchange of vesicles between stem and tumor cells leads to the development of drug resistance and enhances tumor aggression. On the other hand, these fundamental properties of cell communication can open up new therapeutic approaches to the delivery of drugs toward the tumor [1,14,40,41].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, there is also evidence that MSC-EVs are involved in inducing immune responses. For instance, it was reported that AT-MSC-EVs with overexpressed human IL-2, a cytokine that regulates immune cells activation and proliferation, can stimulate the proliferation of CD8+ T-killer cells, thereby effectively killing TNBC cells [ 95 ]. In conclusion, MSC-EVs may act as both stimulatory and/or inhibitory mediators of immune cells in BC.…”
Section: Mesenchymal Stem Cell-derived Extracellular Vesicles In Brea...mentioning
confidence: 99%
“…MSC-MVs can be packed into polycaprolactone (PCL) nanofibers and thus released for a long time, and this apoptotic effect is maintained in cancer cells cultured on PCL-MVs nanofibers, suggesting that AT-MSC-MVs can be used as an in situ inhibitor rather than as a chemo-drug [ 70 ]. Similarly, Chulpanova et al reported that cytochalasin B was also capable of inducing MSCs to release EVs for increasing the yield of EVs [ 95 ]. In addition, BC patients after lumpectomy may require augmentation or surgical cosmetic procedure with scaffolds containing MVs, which have two potential advantages: the ability to fill the cavity created by the removal of cancerous breast tissue as well as causing the death of probable BC cells [ 70 ].…”
Section: The Potential Therapeutic Strategies Of Mesenchymal Stem Cel...mentioning
confidence: 99%